ВОЗМОЖНОСТИ И ПЕРСПЕКТИВЫ ПРИМЕНЕНИЯ МЕЛАТОНИНА ПРИ ИШЕМИЧЕСКОЙ БОЛЕЗНИ СЕРДЦА (ОБЗОР ЛИТЕРАТУРЫ) - З. Д. Михайлова; М. А. Шаленкова (SINAPS LLC, 2014)
The survey considers the role of melatonine in human body and possibility to use exogenic melatonine to correct the effect of abiotic factor with ischemic heart disease. It also includes the experimental and clinical studies to use melatonine in therapy for treatment and prevention.